The Syntax of Class : Writing Inequality in Nineteenth-Century America - Lang, Amy Schrager (Book collections on Project MUSE., 2003)
"The Syntax of Class explores the literary expression of the crisis of social classification that occupied U.S. public discourse in the wake of the European revolutions of 1848. Lacking a native language for expressing class differences, American writers struggled to find social taxonomies able to capture - and manage - increasingly apparent inequalities of wealth and power."--Jacket